The child and the strict father: invoking metaphor in the Safe Schools debate. Issue 6 (1st November 2020) - Wescott, Stephanie
ABSTRACT: The Safe Schools Coalition Australia's teaching resource All of us, or 'Safe Schools', as it became known, was subjected to unrelenting attack from politicians in the Australian Parliament. This paper draws on analysis of the Australian Parliamentary Hansard, examining 18, 000 words spoken about Safe Schools by Senators and Members of Parliament from November 2015 to August 2016. This dataset was interrogated with discourse analysis strategies to examine the ways in which the SSCA's supporters and opponents constructed narratives about Safe Schools, and its intentions and capacities. The analysis found that politicians employed two familiar metaphors: 'the child' and the 'strict father', to meet discursive aims. This paper argues that the invocation of these metaphors had repercussions for the way that the narrative around Safe Schools unfolded and offers Safe Schools as a case study with implications for how to observe future education debates.